'Vagabond-language scrawled on gate-posts': locating home in Evelyn Waugh's travel writing. Issue 1 (2nd January 2018) - Williams, Annabel
ABSTRACT: This essay establishes a framework for comparing Waugh's interwar travelogues with his fiction, by aligning the tropes of home and travel. I will propose that, in his travel writing, and figuratively speaking, Waugh never left England. His impulses to travel, and so his representations of 'abroad', are involved in an entrenched desire to find or create a home. Through readings of Brideshead Revisited, Black Mischief and Remote People, I examine the aporia emerging from a disjunction between the falsely presented factual places and half-imagined fictive places that span genres in Waugh's oeuvre. Heidegger's theorisation of dwelling offers a productive means of analysing the divide between home and homelessness in Waugh. I will suggest that a certain aspect of Waugh's writing – a 'vagabond-language' – destabilises the binaries of remoteness and the homely, the foreign and the native, with which his work is obsessed. Debbie Lisle's investigation of geopolitical discourse will help an understanding of spatial representation in Waugh's work and the textuality of his constructions of home. Though Waugh could neither leave home, nor solve the overwhelming question of deracination for his time, his work encourages us to engage in the remoteness of home, and perhaps to find home in the remote.